PHYSICOCHEMICAL PROPERTIES OF INSTANT PUMPKIN JAVANESE NOODLE GRAVY [Sifat Fisikokimia Saus Bubuk Mi Jawa Instan dari Labu Kering] - Ng Kim Yee; Yusnita Hamzah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
This research was carried out to study the physical and chemical characteristics of pumpkin Javanese noodle gravy prepared in powder form. The finished product is categorized as an instant product as it only needs to be rehydrated with warm water (60°C) before consumption. Five gravy formulations were developed with the incorporation of two types of flour (tapioca and corn flours) as the thickening agent. Physical characteristics including colour and swelling properties of the final products were evaluated. For chemical analysis, ash, moisture, protein, crude fiber, fat and carbohydrate compositions were also determined. For physical analysis, all formulations showed similar colour appearance of the gravy powder including lightness (L), redness (a*) and yellowness (b*). Pertaining swelling properties of the dried gravy, the water absorption index (WAI) values were low (2.0–3.0g/g), while the water solubility index (WSI) were moderate (33.0–50.0%) when evaluated at both hot (85°C) and cold (25°C) water. In termn of chemical compositions, carbohydrate and fat content increased and decreased, respectively with the addition of tapioca and corn flours. The moisture content of the instant gravy increased with the increased of corn flour addition. There were differences in fiber and ash content in all formulations, but no specific trend was observed. Finally, protein content remained the same in all formulations. This current finding provided information of the gravy powder produced. Further analysis on the characteristics of the rehydrated pumpkin Javanese noodle gravy will provide a more complete picture of the finished product.